Pembelajaran Berbasis Saintifik Pada Kelas Inklusif Sekolah Dasar - Oni Oktika Sari; Elsya Meizahwa; Lisa Oktafindari; Hendri Marhadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The scientific approach in inclusive classes is a learning method that allows children with special needs (ABK) and normal children (non-ABK) to work together to be active in learning in class. The aim of this research is to describe sanitary learning in inclusive elementary school classes. This research uses the Literature Review research method. The data analysis technique is carried out descriptively by analyzing and identifying scientific articles to produce a more informative summary. The results of this research show that implementing scientific-based learning consists of five steps, namely through: 1) Observing, 2) Asking, 3) Trying, 4) Reasoning and 5) Communicating. The application of scientific learning in inclusive classes is still not implemented optimally, especially in communication activities. Students in inclusive scientific learning classes are still unable to communicate deftly and their behavior tends to be hyperactive or very passive.